Antioxidant and anti-inflammatory dietary supplements in the treatment of osteoarthritis: a scoping review - Sakinah, Harith; Mohd Razif, Shahril; Norshazila, Shahidan (2019)
Background Increasing evidence reported that inflammation and oxidative stress is a key mediator of osteoarthritis (OA) joint pathology, therefore usage of dietary supplements targeting inflammation and oxidative stress in OA could be a rewarding therapeutic strategy. This study aims to explore the efficacy of antioxidant and anti-inflammatory dietary supplements used to manage OA. Methods A methodological framework proposed by Arksey and O'Malley was used to conduct this staging review. An electronic database search of English academic articles was conducted using PubMed, MEDLINE and ScienceDirect from 2000 to 2018. Randomized controlled trials (RCTs) of OA with parallel groups by comparing dietary supplements with placebo were eligible for inclusion. Out of 69150 study identified, a total of 41 studies were included. Result A total of 24 antioxidant or anti-inflammatory dietary supplements were identified. There were 3325 (1740 in the treatment group and 1585 in the placebo group) respondents which aged a 25 years old in which 2284 were female and 996 were male respectively. The majority of the studies recruited participants with knee OA (n = 33) with follow-up duration of 3-32 weeks Overall, most of the dietary supplements demonstrated beneficial effect on clinical signs and symptoms. In contrast, Aquamin supplementation did not exert positive impacts on OA management. Also. inconsistent findings were observed in green-lipped mussel (GLM) extract. vitamin E, methylsulfonylmethane (MSM). liquorice flavonoid od (LEO). ginger. willow bark extract and rose hip supplementation. Discussion The bioactive compounds found in dietary supplements that demonstrated positive impacts are predominantly polyphenols Polyphenols are found abundantly in plants and vegetables with strong anti-inflammatory and free radical scavenging antioxidant activity. In summary, since there is no cure for OA currently. the role of anti-inflammatory and antioxidant dietary supplements cannot be ignored since they can provide pain and symptoms alleviation.